Constitutive Interests in CNN Media Framing and Instagram's Shadow Banning Related to Israel's Aggression against Palestine 2023-2024 - Rahayu, Dini Septyana; Susilowati, Ida; Huzaeny, Roziqk Heally (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This study aims to explain CNN's media framing and Instagram's shadow-banning censorship policy related to Israel's aggression against Palestine since October 2023 as an action that contains a constitutive construction of interests. Through CNN's media coverage, the situation between Palestine and Israel is not described as an aggression, occupation, or genocide but as a conflict that occurred due to Hamas's attack on Israel. CNN even only uses diction that places Israel as the party being attacked and limits exposure to the loss of life in Palestine caused by Israel's aggression. The international community sympathises and provides their views regarding the developing situation but is hampered by Instagram's censorship policy through shadow banning. By using an interpretive approach to observe CNN's reporting and Instagram's shadow banning, the results of this study show that both contain US-Israeli constitutive interests in manipulating and controlling international perceptions. This refers to the interest in constructing intersubjective understandings related to Israel's positive image, which simultaneously eliminates Palestine's existence as a nation-state.Keywords: CNN; Instagram; Israel; Knowledge Constitutive Interests; Media Framing; Palestina; Shadow Banning